Cyclic fatigue resistance, number of uses, and morphological/chemical analysis of RCS Rainbow Files, VDW Rotate and ProTaper Ultimate: in vitro study - da Silva, Tayná Lopes [UNESP]; Lopes, Patrícia Carla [UNESP]; de Rezende, Mírian Galvão Bueno; Abu Hasna, Amjad [UNESP] (Springer Nature, 2025)
BackgroundThis in vitro study aimed to evaluate the cyclic fatigue resistance and number of uses post-sterilization of three rotary systems: ProTaper Ultimate, VDW Rotate, and RCS Rainbow Files. The study also sought to assess surface topography and chemical composition using scanning electron microscopy (SEM), and Energy-Dispersive Spectroscopy (EDS).MethodsThe cyclic fatigue resistance was evaluated using simulated artificial canal. The number of uses post-sterilization was evaluated using ninety extracted human upper and lower molars selected under strict inclusion criteria. Standardized root canal instrumentation was performed, followed by Scanning Electron Microscopy (SEM) at four moments including: unused instrument (baseline), after the 1st, 2nd and 3rd uses, and Energy-Dispersive Spectroscopy (EDS) analysis only for unused instruments. The data were subjected to a normality test, followed by one-way ANOVA and Tukey’s post-hoc analysis, with a significance level set at α ≤ 0.05.ResultsIt was found that RCS Rainbow One Files and VDW Rotate exhibited significantly greater cyclic fatigue resistance compared to ProTaper Ultimate (P = 0.0006). Despite this, all systems exhibited increased surface deterioration and susceptibility to fracture after repeated uses and autoclave sterilization, without significant difference in total fractures number among the groups; SEM analysis revealed progressive surface deterioration, microcrack formation, and deformation after each use, particularly after the second and third uses; and EDS analysis indicated the presence of residual elements such as carbon, aluminum, and oxygen, suggesting contamination and potential material instability.ConclusionRCS Rainbow One Files and VDW Rotate demonstrated superior cyclic fatigue resistance compared to ProTaper Ultimate; however, all systems became increasingly prone to fracture following repeated clinical use and autoclave sterilization, without significant differences in total fractures. These findings reinforce the need for cautious reuse of NiTi rotary instruments, as repeated use may compromise safety and treatment outcomes.